Flexible Work Arrangements: Conceptualizations and International Experience - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2005)
The book Flexible Work Arrangements: Conceptualizations and International Experience, by Isik Urla Zeytinoglu, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Flexible hours; International comparisons; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z